Clinical Supervision Model for Building Sciences Teacher's Professionalism in Curriculum Implemention 2013 - Rahmawati - Syamsuddin (Jurnal Pendidikan Fisika, 2019)
The aim of developing this supervision model is to produce a science education supervision model that is able to help parties or stakeholders who take responsibility in the process of building teacher professionalism in implementing the 2013 curriculum into science learning (IPA). To be able to measure the level of quality of the 2013 curriculum implementation in science learning in junior high schools, an ongoing monitoring and evaluation effort is needed. One effort that can be done to maintain the quality and quality of science learning that implements the 2013 curriculum is through the implementation of clinical supervision of science learning. The purpose of science learning quality assurance must be done as a form of concern in ensuring students get science learning in accordance with the objectives and levels derived from the 2013 science curriculum.Keywords: The 2013 Curriculum, Clinical Supervise Model, Monitoring And Evaluation, Quality ControlTujuan pengembangan model supervisi ini adalah untuk menghasilkan suatu model supervisi pendidikan IPA yang mampu membantu pihak atau stakeholder yang ikut serta bertanggung jawab dalam proses membangun profesionalisme guru dalam mengimplementasikan kurikulum 2013 ke dalam pembelajaran sains (IPA). Untuk dapat mengukur tingkat kualitas implementasi kurikulum 2013 dalam pembelajaran IPA di sekolah-sekolah SMP, maka diperlukan suatu upaya monitoring dan evaluasi yang berkesinambungan. Salah satu upaya yang dapat dilakukan untuk menjaga kualitas dan mutu pembelajaran IPA yang mengimplementasikan kurikulum 2013 adalah melalui pelaksanaan supervisi klinis pembelajaran IPA. Tujuan mengapa harus dilakukan penjaminan mutu pembelajaran IPA adalah sebagai bentuk kepedulian dalam menjamin peserta didik mendapatkan pembelajaran IPA sesuai dengan tujuan dan tingkatannya yang diturunkan dari kurikulum IPA 2013.Kata kunci: Kurikulum Ipa 2013,Model Supervise Klinis, Monitoring dan Evaluasi, Penjaminan Mutu